Implementing CLIL in Schools: The Case of the GoCLIL Project in Portugal - Ellison, Maria (2018)
Content and Language Integrated Learning (CLIL), an educational approach in which an additional language is used to teach school subjects, has become increasingly widespread within state schools across Europe since the acronym was coined in the mid-nineties. This now includes Portugal where CLIL activity across educational levels has been growing in recent years. Like other national contexts in Europe, this has also been through the grassroots initiatives of individual schools keen to influence positive change in educational practices and reap the benefits which CLIL is purported to bring about. One such case is the GoCLIL project at Escola Secundária Dr. Joaquim Gomes Ferreira Alves in Valadares, Vila Nova de Gaia, which has been operating a CLIL programme through English since the academic year 2013-2014. This article outlines fundamentals of implementing CLIL in schools and provides an overview of the strengths, weaknesses, opportunities and threats (SWOT) of the case. It uses data collected from questionnaires administered to teachers, pupils and parents, lesson observations, pupil focus groups, and teacher reflections obtained during the ongoing monitoring process led by the Faculty of Arts and Humanities of the University of Porto. The data contribute to the rich description of the project from which it has been possible to identify and compare findings across years, as well as factors which have contributed to its sustainability. Insights gained from this case study will be interesting and potentially useful for schools which are considering setting up a project of this kind.